Development Of A Solar Powered IoT Based Landslide Detection System - Dwiyanto Dwiyanto; Iman Hidayat; Rizky Alamsyah; Ninik Sri Lestari; Givy Devira Ramadi; Sukirno Sukirno (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The surfaces of three major tectonic plates the Eurasian Plate, the Indo Australian Plate, and the Pacific Plate intersect in Indonesia. This condition creates a high risk of earthquakes and landslides in areas located at these plate boundaries. The urgency of this research lies in developing a landslide detection device to help communities living in landslide-prone areas remain alert to disasters that may occur at any time. The objective of this study is to develop an Internet of Things (IoT)-based landslide detection device powered by solar energy. This device does not rely on external power sources but utilizes solar energy as its primary power supply. The research employs an experimental method. The steps include problem identification, literature review, system development methodology, design and application development, testing, and analysis of test results.Landslide detection is carried out using vibration sensors to detect ground tremors that may indicate a landslide, tilt sensors to monitor changes in ground inclination, and soil moisture sensors to measure soil humidity. An Arduino microcontroller processes data from the sensors and transmits signals to the warning system, while solar panels generate electrical energy from sunlight. The use of solar cells is optimized by calculating the required energy capacity to operate the sensors, Arduino board, and early warning system.